Experiment study on the performance of the dual cycle air dehumidification system (DCADS) - Ng, Joseph Si Hao (Nanyang Technological University, 2021)
Humidity control plays an important role in establishing and maintaining a comfortable indoor environment. In these years, many advanced techniques have been employed to improve the capacity and energy efficiency of the air dehumidification system, such as liquid desiccant dehumidification system, advanced control, and optimization. Different from conventional AHUs, DCADS uses higher temperature central plant chilled water or VRF refrigerant to pre-cool the air and then use a high-efficiency internal heat pump to dehumidify the air to the required humidity ratio and reheat the air before discharge. In this project, a dual cycle air dehumidification system will be developed to test the performance of air dehumidification. Experiment study should be carried out to investigate the factors that affect the performance of the developed air dehumidification system.